2006
DOI: 10.1002/per.572
|View full text |Cite
|
Sign up to set email alerts
|

Personality, creativity and latent inhibition

Abstract: The current study set out to investigate the relationship between creativity, multidimensional schizotypy and personality more generally. This was achieved by analysing scores on a range of personality scales and measures of creativity, where it was found that the creativity measures were more closely related to asocial-schizotypy than positiveschizotypy. The study also sought to test Eysenck's prediction (1993, 1995) that, given the putative relationship between creativity and psychosis-proneness, high psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 53 publications
(72 reference statements)
3
33
1
3
Order By: Relevance
“…Green and Williams (1999) did not find evidence for this relationship. Wuthrich and Bates (2001) and Burch, Hemsley, Pavelis, and Corr (2006) did not confirm the hypothesis that lower LI may mediate the relationship between various aspects of schizotypy, other personality traits and creativity.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Green and Williams (1999) did not find evidence for this relationship. Wuthrich and Bates (2001) and Burch, Hemsley, Pavelis, and Corr (2006) did not confirm the hypothesis that lower LI may mediate the relationship between various aspects of schizotypy, other personality traits and creativity.…”
Section: Discussioncontrasting
confidence: 67%
“…There is empirical evidence that schizotypal personality traits are associated with creativity, although the magnitude and pattern of the relationship are not consistent across studies and depend on the instruments used for the assessment (e.g.. Batey & Fumham, 2008;Burch, Pavelis, Hemsley, & Corr, 2006;Cox & Leon, 1999;Nelson & Rawlings, 2010;Nettle, 2006;Schuldberg, 1990). In addition, the O-LIFE questionnaire overlaps with the dimensions of other personality measures (Mason et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Later on, Carson, Peterson, and Higgins (2003) revealed that decreased latent inhibition is associated with the originality score of the divergent thinking tasks as well as with the overall divergent thinking in high-functioning people. Thus, the Eysenckian proposition that reduced latent inhibition links to creativity was supported by empirical evidence (but see Burch, Hemsley, Corr, & Pavelis, 2005). Eysenck (1995) has shown that RT is the main response measure in negative priming tasks.…”
Section: Attention and Creativitymentioning
confidence: 89%
“…Burch i saradnici nisu potvrdili povezanost između psihoticizma i kreativnosti (Burch et al, 2005). Chávez-Eakle i saradnici nalaze da visoko kreativne osobe ostvaruju generalno niske skorove na merama psihopatologije, da nema statistički značajnih razlika u izraženosti psihopatoloških simptoma u odnosu na kontrolnu grupu i da postoji visoka negativna korelacija između kreativnosti i psihopatologije.…”
Section: Odnos Kreativnosti I Mentalnih Poremećajaunclassified
“…Potencijalni faktori zajedničke vulnerabilnosti ostvarili su značajnu predikciju indikatora kreativnih potencijala, što ukazuje na to da otvorenost prema iskustvu, niža latentna inhibicija i veća sklonost da se izveštava o sinestetskim iskustvima zaista predstavljaju faktore relevantne za kreativnost, što potvrđuju i druga istraživanja (Burch et al, 2005;Car-son, 2011;Ramachandran, 2001, prema Flaherty, 2011. Takođe, efikasnost radne memorije pokazala se kao značajan prediktor kreativnosti, što predstavlja tendenciju koja je takođe u skladu sa predikcijama modela -da osobe koje ostvaruju veće postignuće na merama kreativnih potencijala manifestuju i veću efikasnost radne memorije (Carson, 2011).…”
Section: Diskusijaunclassified